2018
DOI: 10.1002/pat.4414
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of poly (1,6‐hexamethylene oxamide‐co‐m‐xylene oxamide) copolymers

Abstract: To modify the properties of poly (hexamethylene oxamide) (PA62), m-xylylene diamine (MXD) was introduced into the polyamide main chain. A series of high molecular weight PA62/MXD2 were synthesized via a two-step method. The chemical structure of polymer was analyzed by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance spectroscopy, and the results confirmed the formation of PA62/MXD2. DSC test showed that the T m of the copolymers were decreased as the molar contents of MXD in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…According to Figure 5 ( a ) , ran‐PA6T/62 displayed an obvious glass transition temperature ( T g ) and a broad melting peak, which indicated that with the incorporation of 6 T units, the crystallization of 62 units was strongly restrained and resulted in low crystallinity. Compared with ran‐PA6T/62 ( T m = 294°C, ΔH f = 17 J g −1 , T c = 243°C, ΔH c = 18 J g −1 ), which possesses decreased crystallinity, 27–29 the molecular chain arrangement of alt‐PA6T/62 is more regular, and the corresponding crystal properties and thermal properties are improved. These results demonstrate that PA6T/62 alternating copolyamide displayed both high temperature resistance and excellent processing properties.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Figure 5 ( a ) , ran‐PA6T/62 displayed an obvious glass transition temperature ( T g ) and a broad melting peak, which indicated that with the incorporation of 6 T units, the crystallization of 62 units was strongly restrained and resulted in low crystallinity. Compared with ran‐PA6T/62 ( T m = 294°C, ΔH f = 17 J g −1 , T c = 243°C, ΔH c = 18 J g −1 ), which possesses decreased crystallinity, 27–29 the molecular chain arrangement of alt‐PA6T/62 is more regular, and the corresponding crystal properties and thermal properties are improved. These results demonstrate that PA6T/62 alternating copolyamide displayed both high temperature resistance and excellent processing properties.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, polyoxamides with η int = 1.9 were prepared. Recently, much research on polyoxamides has been reported by utilizing this two‐step polymerization method, and high‐performance polyoxamides have been successfully synthesized 24–29 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations